Slip effects on squeezing flow of nanofluid between two parallel disks - Das, Kalidas; Jana, Subham; Acharya, Nilangshu (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the influence of temperature and wall slip conditions on the unsteady flow of a viscous, incompressible and electrically conducting nanofluid squeezed between two parallel disks in the presence of an applied magnetic field is investigated numerically. Using the similarity transformation, the governing coupled partial differential equations are transformed into similarity non-linear ordinary differential equations which are solved numerically using the Nachtsheim and Swigert shooting iteration technique together with the sixth order Runge -Kutta integration scheme.
Keywords: nanofluid; slip effects; squeezing flow; magnetic field